Coronary sinus neuropeptide y levels and adverse outcomes in patients with stable chronic heart failure - Ajijola, O; Chatterjee, N; Gonzales, M; Gornbein, J; Liu, K; Li, D; Paterson, D; Shivkumar, K; Singh, J; Herring, N (American Medical Association, 2019)
Importance: Chronic heart failure (CHF) is associated with increased sympathetic drive and may increase expression of the cotransmitter neuropeptide Y (NPY) within sympathetic neurons. Objective: To determine whether myocardial NPY levels are associated with outcomes in patients with stable CHF. Design, Setting, and Participants: Prospective observational cohort study conducted at a single-center, tertiary care hospital. Stable patients with heart failure undergoing elective cardiac resynchronization therapy device implantation between 2013 and 2015. Main Outcomes and Measures: Chronic heart failure hospitalization, death, orthotopic heart transplantation, and ventricular assist device placement. Results: Coronary sinus (CS) blood samples were obtained during cardiac resynchronization therapy (CRT) device implantation in 105 patients (mean [SD] age 68 [12] years; 82 men [78%]; mean [SD] left ventricular ejection fraction [LVEF] 26% [7%]). Clinical, laboratory, and outcome data were collected prospectively. Stellate ganglia (SG) were collected from patients with CHF and control organ donors for molecular analysis. Mean (SD) CS NPY levels were 85.1 (31) pg/mL. On bivariate analyses, CS NPY levels were associated with estimated glomerular filtration rate (eGFR; rs = -0.36, P < .001); N-terminal-pro hormone brain natriuretic peptide (rs = 0.33; P = .004), and LV diastolic dimension (rs = -0.35; P < .001), but not age, LVEF, functional status, or CRT response. Adjusting for GFR, age, and LVEF, the hazard ratio for event-free (death, cardiac transplant, or left ventricular assist device) survival for CS NPY ≥ 130 pg/mL was 9.5 (95% CI, 2.92-30.5; P < .001). Immunohistochemistry demonstrated significantly reduced NPY protein (mean [SD], 13.7 [7.6] in the cardiomyopathy group vs 31.4 [3.7] in the control group; P < .001) in SG neurons from patients with CHF while quantitative polymerase chain reaction demonstrated similar mRNA levels compared with control individuals, suggesting increased release from SG neurons in patients with CHF. Conclusions and Relevance: The CS levels of NPY may be associated with outcomes in patients with stable CHF undergoing CRT irrespective of CRT response. Increased neuronal traffic and release may be the mechanism for elevated CS NPY levels in patients with CHF. Further studies are warranted to confirm these findings. Trial Registration: ClinicalTrials.gov identifier: NCT01949246.